The Establishment of “Belt and Road” International Investment Disputes Settlement Institution - Lu, Yang (Journal of Law and Commerce, 2019)
In the context of the growth of regional international investment disputes (IIDs) caused by the Belt and Road (B&R) initiative, having a third-party settlement will play an important role in IIDs. Currently, the B&R countries have mostly selected ICSID as the IIDs settlement institution in their Bilateral Investment Treaties (BITs), which makes cases where a B&R country is respondent to be handled by nationals of countries outside the B&R area. Therefore, it is necessary to establish a B&R IIDs Settlement Institution, for the purpose of optimizing the current situation of IIDs settlement in the B&R region, dealing with the constantly-increasing regional IIDs, better protecting geographical investments, and facilitating China to participate in and further guide the reconstruction of international investment regulations. Moreover, the feasibilities in law, platform and resources for its establishment have been available. With respect to the path option, we should take the Asia Infrastructure Investment Bank as a platform to draft a convention, take the ICSID Convention as a reference for structure and system innovation, and devote great efforts to driving B&R countries to conclude the convention.